A risk-based approach to reduction of warm air infiltration for energy efficiency optimization in a cold storage system-a case study of a fruit packaging plant - Peter Kibagendi Mokaya; James Wakiru; Josephat Tanui (International Journal of Research in Industrial Engineering)
Warm air infiltration is a hidden phenomenon that can go unnoticed for weeks, months, or even years in cold storage envelopes. It is a common source of energy wastage that can be explored to achieve significant energy and cost savings. This research assesses warm air infiltration into fruit cold storages using a case study approach for an international fruit exporter based in Kenya, covering baseline study, root cause analysis, and developing a risk-based mitigation strategy to minimize the infiltration rates. Thermal graphic measurements, electricity bills, and on-site observation of the operation patterns provided source data. An Ishikawa diagram and a risk-based Failure Mode and Effect Analysis (FMEA) were used to identify and prioritize root causes, respectively, and a modified decision tree was then utilized to structure the mitigation strategy. The study established a lack of awareness of cold storage operations, irregular and untimed maintenance of components, broken door seals, and inconsistency in the frequency of cold storage door openings as the critical root causes for the warm air-infiltration challenge. It was further revealed that cold storage facilities need to take advantage of the available sensory and operational data to introduce maintenance management systems, temperature-airflow monitoring systems, and environmental control devices to complement the functionality of cold storage components. To operate fruit cold storages optimally and efficiently, facilities management must comprehensively understand the sources of temperature variations and adopt mitigation strategies that minimize warm air infiltration. There is no one-size-fits-all approach to reducing warm air infiltration; thus, both systemic and behavioral approaches must be adopted and integrated into cold storage operations.